2016
DOI: 10.5130/ajceb.v16i4.4984
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing e-Procurement adoption in the Nigerian building industry

Abstract: Against the backdrop of increasing adoption of e-Procurement in supply chain management, there is a need for adequate knowledge of the factors that influence the decision by organizations in the building industry to use e-Procurement. This study aims to fill the knowledge gap through investigating the factors influencing e-Procurement adoption based on the data sourced in a questionnaire survey involving 213 organizations in the building industry. The survey was conducted between June and November 2015 in Nige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 11 publications
1
37
0
Order By: Relevance
“…According to Croom and Johnston [11], e-Procurement systems are simply the application, tools, and technologies used to carry out procurement activities via the Internet. This definition was corroborated by [7,12] in that, the main instrument that makes e-Procurement possible is the innovation of the Internet. In the context of construction activities, e-Procurement involves placing, submitting, and receiving tenders, sourcing and ordering of materials, exchanging emails between construction clients and contractors/suppliers for contract management or other transactions via the internet [13].…”
Section: Review Of Literaturementioning
confidence: 89%
See 2 more Smart Citations
“…According to Croom and Johnston [11], e-Procurement systems are simply the application, tools, and technologies used to carry out procurement activities via the Internet. This definition was corroborated by [7,12] in that, the main instrument that makes e-Procurement possible is the innovation of the Internet. In the context of construction activities, e-Procurement involves placing, submitting, and receiving tenders, sourcing and ordering of materials, exchanging emails between construction clients and contractors/suppliers for contract management or other transactions via the internet [13].…”
Section: Review Of Literaturementioning
confidence: 89%
“…This represented 55 percent of the total questionnaires sent out by the researchers. The design of the questionnaire instrument was mainly in two sections of the background information of the respondents and the 21 critical success factors (CSFs) identified from [7,18,21]. The variables of the CSFs were tested using Cronbach alpha reliability which gave a value of 0.880 which is greater than the acceptable value of 0.70 as shown in [24].…”
Section: Minimum Sample Size Nmentioning
confidence: 99%
See 1 more Smart Citation
“…An integration of e-procurement in the Ghanaian public sector will allow the use of a single portal where the registered agencies under the government sector can exchange information among themselves in relation to procurement processes [32]. This allows for greater visibility of public procurement processes in bid to provide opportunities for negotiation [33]. Also, computerized transactions present inclusive, precise assessment and audit which gives room for users to monitor orders and address challenges as and when the need arises [34].…”
Section: Information Sharingmentioning
confidence: 99%
“…5 Therefore, e-procurement in the building industry can be described as the use of electronic communication technologies and transaction processes to support From the existing studies, we know that, apart from facilitating easy documentation and making exchange of information more accurate and efficient and at the lowest transaction cost 20,21 , e-procurement also ensures transparency and accountability in construction procurement. 22 The existing studies 23,24 also reveal that several factors related to firms/organizations, the attributes of e-procurement technologies, and the environment in which adopters operate can influence the adoption of e-procurement. Among these factors, Rezgui et al 25 observed that organizational issues are among the key factors affecting the adoption of new technologies in the construction sector.…”
Section: Introductionmentioning
confidence: 99%